A physiologically-based flow network model for hepatic drug elimination I: regular lattice lobule model - Rezania, Vahid; Marsh, Rebeccah; Coombe, Dennis; Tuszynski, Jack A. (My University, 2013)
We develop a physiologically-based lattice model for the transport and metabolism of drugs in the functional unit of the liver, called the lobule. In contrast to earlier studies, we have emphasized the dominant role of convection in well-vascularized tissue with a given structure. Estimates of convective, diffusive and reaction contributions are given. We have compared drug concentration levels observed exiting the lobule with their predicted detailed distribution inside the lobule, assuming that most often the former is accessible information while the latter is not.
Keywords: drugs; lattice models